Medya Ekonomisi ve Başrol Oyuncuları: Bugünün Ve Yarının Medya Aktörlerinin Gözünde Reklamcılar Ve Tüketiciler - Kuyucu, Mihalis (The Turkish Online Journal of Design Art and Communication, 2014)
Media today is one of the most increasing industry of the world. The developments of this industry showed that this field has a very serious economy. This paper express what’s media economy about and how it differs from the general economy. This study consist of two parts. In the first part of the study there is a conceptual research for media economics, meaning, history and difference from general economy. The second part of the study consist of the findings of the deep interviews done for the research. The aim of this study is to make an evaluation on the four important key factors, media company owners, consumers, advertisers and media workers, of media economics and their importance within media industry. There is a determination about the most important elements of media economics effecting media industry and how this will effect media economics in the future. For this there has been done interviews to two different targeted segments: Today’s media environment and future’s media environment. In the first group there has been done interviews with 41 media workers. In the second target group there has been done interviews in deep with 41 communication faculty students. Each were asked to express which of these four factors dominates media economics more and why. At the end of the research both today’s and future’s media environment expressed that advertisers are the most important element in media economics. In the conclusion part of the study there is a discussion for the four key factors that Picard had expressed in media economics, their competition that they face within each and their future roles in media economics.
Keywords: Medya Ekonomisi; Medya Endüstrisi; Reklam; Ekonomi; Picard; Media Economics; Media Industry; Advertising; Economics